Implementation of Scabies Prevention in Islamic Boarding Schools through the ABC Program (sAntri Bebas sCabies) - Lia Kurniasari; Suprayitno Suprayitno; Shafa Annisa Zein; Desca Gema Misvialita; Indri Puspita Sari Firdani; Nurul Novita Sari; Nurjanah Nurjanah; Sri Widianingsih; Yudi Riswana (Faculty of Public Health, University of Jember in collaboration with PERSAKMI, 2022)
Scabies is a disease caused by Sarcoptes scabies. This disease can occur in men and women in dense areas and poor sanitation. The main causes that cause the emergence of these mites are the influence of environmental factors that are densely population and cleanliness is not maintained. One example of a densely population environment is boarding schools and dormitories because of the habit of living together so that if one has been infected, the other will easily be infected. Empowerment Programs ABC (students free from scabies disease) is one form of community empowerment that aims to reduce the number of scabies and improve the health of Islamic boarding school students. The method used is to provide health education about scabies and personal hygiene, the environment and cadre training to carry out health monitoring programs in the boarding school environment with a total of forty four students. And as a result of this activity there was an increase in knowledge of 3.28%.